Nutrient and Chemical Analysis of Fruiting Bodies of a Cultivar of the Chinese Caterpillar Mushroom, Ophiocordyceps sinensis (Ascomycetes) - Fung, Shin Yee; Cheong, Peter Chiew Hing; Tan, Nget Hong; Ng, Szu Ting; Tan, Chon Seng (Begell House, 2018)
A cultivar of fruiting bodies of Ophiocordyceps sinensis (FBOS; OCS02) was analyzed for nutrients, bioactive compounds, and heavy metal content to showcase its potential as a competitive, sustainable, and safe alternative to wild types and other cultivars. A previous 28-day subacute toxicity study showed that doses up to 1 g · kg−1 did not cause any adverse effects in Sprague-Dawley rats. The OCS02 cultivar contained large amounts of cordycepin, polysaccharides, and essential and semi-essential amino acids (0.66, 482.80, 99.02, and 101.04 g · kg−1, respectively) compared with levels reported in wild types and in cultivated mycelia. β-1,3/1,6-glucan content was considerably high at 342.50 g · kg−1. The potassium level (5.14 g ·kg−1) tied in well with the low sodium content (0.121 g · kg−1)—6 times lower than amounts in wild types. We found no detectable levels of heavy metals such as lead, arsenic, cadmium, and mercury. The major amino acids found in FBOS (OCS02 cultivar) were arginine, lysine, serine, and threonine at 45.20, 20.30, 18.60, and 18.20 g · kg−1, respectively. The cultivated FBOS (OCS02 cultivar) is a comparable alternative to wild-type and other cultivated strains of O. sinensis. It has potential as a nutraceutical to meet market demand.